Biotinidase Deficiency, a Rare but Treatable Inborn Error of Metabolism - Rup, Amit Ranjan; Dash, Arun Kumar; Behera, Jyoti Ranjan; Patanaik, Sibabratta; Jain, Mukesh Kumar (Journal of Nepal Paediatric Society, 2021)
Biotinidase deficiency (BTD) is a rare inherited metabolic disorder with predominant dermatogical and neurological manifestations, which if untreated leads to severe neurological sequelae. Early diagnosis and prompt treatment with biotin prevents further progression of neurological symptoms and resolution of cutaneous features. We report an interesting case of four and half year male child presenting with seizures, developmental delay with non resolving extensive skin lesions and alopecia, diagnosed as BTD and successfully treated.